Biomarkers of Rheumatoid Arthritis–Associated Interstitial Lung Disease1. Issue 1 (January 2015) - Chen, Juan; Doyle, Tracy J.; Liu, Yongliang; Aggarwal, Rohit; Wang, Xiaoping; Shi, Yonghong; Ge, Sheng Xiang; Huang, Heqing; Lin, Qingyan; Liu, Wen; Cai, Yongjin; Koontz, Diane; et al.
<x xml:space="preserve">Abstract</x> Objective Interstitial lung disease (ILD) is a relatively common extraarticular manifestation of rheumatoid arthritis (RA) that contributes significantly to disease burden and excess mortality. The purpose of this study was to identify peripheral blood markers of RA‐associated ILD that can facilitate earlier diagnosis and provide insight regarding the pathogenesis of this potentially devastating disease complication. Methods Patients with RA who were enrolled in a well‐characterized Chinese identification cohort or a US replication cohort were subclassified as having RA–no ILD, RA–mild ILD, or RA–advanced ILD, based on high‐resolution computed tomography scans of the chest. Multiplex enzyme‐linked immunosorbent assays (ELISAs) and Luminex xMAP technology were used to assess 36 cytokines/chemokines, matrix metalloproteinases (MMPs), and acute‐phase proteins in the identification cohort. Unadjusted and adjusted logistic regression models were used to quantify the strength of association between RA‐ILD and biomarkers of interest. Results MMP‐7 and interferon‐γ–inducible protein 10 (IP‐10)/CXCL10 were identified by multiplex ELISA as potential biomarkers for RA‐ILD in 133 RA patients comprising the Chinese identification cohort (50 RA–no ILD, 41 RA‐ILD, 42 RA–indeterminate ILD). The findings were confirmed by standard solid‐phase sandwich ELISA in the Chinese identification cohort as well as an independent cohort of US patients with RA and different stages of ILD (22 RA–no ILD, 49 RA‐ILD, 15 RA–indeterminate ILD), with statistically significant associations in both unadjusted and adjusted logistic regression analyses. Conclusion Levels of MMP‐7 and IP‐10/CXCL10 are elevated in the serum of RA patients with ILD, whether mild or advanced, supporting their value as pathogenically relevant biomarkers that can contribute to noninvasive detection of this extraarticular disease complication.